2013
DOI: 10.1186/1472-6882-13-367
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of the clinical characteristics of hospitalized children with community-acquired pneumonia in eight eastern cities in China

Abstract: BackgroundCommunity-acquired pneumonia in children is common in China. To understand current clinical characteristics and practice, we conducted a cross-sectional study to analyze quality of care on childhood pneumonia in eight eastern cities in China.MethodsConsecutive hospital records between January 1, 2010 and December 31, 2010 were collected from 13 traditional Chinese medicine (TCM) and western medicine (WM) hospitals in February, May, August, and November (25 cases per season, 100 cases over the year), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…Cough was the most common presenting symptom in the present study, as it occurred in 99.2% of patients, while fever occurred in 87.7% of patients. It was also found that wheezes was present in 75.4% of the studied cases, which is similar to what was reported by Wang et al and Al-Dabbagh et al (11,14) . This is may be due to mixed viral/bacterial pneumonia or associated bronchial asthma, and the fact that most of the cases in both studies were infants who are prone to wheezes because of small caliber peripheral airways.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Cough was the most common presenting symptom in the present study, as it occurred in 99.2% of patients, while fever occurred in 87.7% of patients. It was also found that wheezes was present in 75.4% of the studied cases, which is similar to what was reported by Wang et al and Al-Dabbagh et al (11,14) . This is may be due to mixed viral/bacterial pneumonia or associated bronchial asthma, and the fact that most of the cases in both studies were infants who are prone to wheezes because of small caliber peripheral airways.…”
Section: Discussionsupporting
confidence: 80%
“…The current study found that male to female ratio of pneumonia cases was 1:1, which is lower than reported by Wang et al 2013 (11) ,which was 1.4: 1.Lifestyle, behavioral, and socioeconomic differences between males and females may explain the observed findings.…”
Section: Discussioncontrasting
confidence: 55%
“…In many children with CAP, more than 2 pathogens may be identified in diagnostic testing, including viral and bacterial combinations, which makes it difficult to determine the significance of any single pathogen. 55,72 2) There were constraints in determining etiologies based on available methods. Most bacterial pathogens were isolated from NA and sputum cultures; this could represent colonization rather than infection.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may be the result of the widespread use of third-generation cephalosporins. A cross-sectional study conducted in 2013 showed that the antibiotics commonly used by decreasing frequency were macrolides, third generation cephalosporins, second-generation cephalosporins, first generation cephalosporins, and β-lactams in Chinese hospitals [ 20 ]. In fact, the situation of inappropriate use and abuse of cephalosporins has been reported in China [ 21 – 22 ].…”
Section: Discussionmentioning
confidence: 99%